2017
DOI: 10.1007/s10068-017-0059-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ozone treatment on physicochemical properties of Korean wheat flour

Abstract: The objective of this study was to investigate the effects of ozone treatment on the physicochemical properties of Korean wheat flour. Wheat flour samples were treated with ozone gas at 120 ppm for 15, 30, 45, and 60 min. Color b value, pH, and mold of flour decreased as exposure time to ozone increased. The water absorption index, peak viscosity, and final viscosity of flour increased by ozone treatment. Photomicrographs of flour suspensions under polarized light showed granules tended to lose birefringence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 26 publications
2
20
0
2
Order By: Relevance
“…Prolonged high‐concentration ozone exposure led to the degradation of the gluten structure through oxidation, which might explain the lower protein content in treated wheat grain. The causative role of protein oxidation is supported by previous studies . After ozone treatment with 2.44 g m −3 for up to 7.79 h, it was observed that the 1000‐kernel weight of treated grain, as compared to untreated grain, was reduced and that the hardness was increased.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Prolonged high‐concentration ozone exposure led to the degradation of the gluten structure through oxidation, which might explain the lower protein content in treated wheat grain. The causative role of protein oxidation is supported by previous studies . After ozone treatment with 2.44 g m −3 for up to 7.79 h, it was observed that the 1000‐kernel weight of treated grain, as compared to untreated grain, was reduced and that the hardness was increased.…”
Section: Resultssupporting
confidence: 59%
“…The causative role of protein oxidation is supported by previous studies. 27,39 After ozone treatment with 2.44 g m −3 for up to 7.79 h, it was observed that the 1000-kernel weight of treated grain, as compared to untreated grain, was reduced and that the hardness was increased. Reduction of surface moisture as a result of kernel oxidation due to ozone treatment might harden the grain.…”
Section: Comparative Post-treatment Wheat End-use Quality Physicochemmentioning
confidence: 99%
“…Similar results were also reported by Mei et al (2016) who found a decrease in wet gluten when ozone treatment time was further increased, which destroyed the gluten structure and the water-holding capacity decreased rapidly. There was a similar report in Lee et al (2017). The quality of wheat gluten is not only related to WGC and GI, but to the Sedimentation Volume (SV), the higher the SV of wheat flour, the better the quality of gluten protein and flour (Ibanoglu, 2002).…”
Section: Gluten Qualitiesmentioning
confidence: 74%
“…Negatively charged starch molecules may then repel each other, increasing granule swelling during gelatinization (Sandhu et al, ). For these reasons, the peak viscosity and final viscosity were both increased by ozone treatment (Lee, Kim, Kwak, Lim, & Kim, ). The setback value is more likely related to starch retrogradation, especially that of amylose.…”
Section: Introductionmentioning
confidence: 99%